Land-use changes may explain the recent range expansion of the Black-shouldered Kite Elanus caeruleus in southern Europe - Balbontín, Javier; Negro, Juan José; Sarasola, José Hernán; Ferrero, Juan José; Rivera, Domingo (Ibis, 2008)
Occasional observations of Black-shouldered Kites Elanus caeruleus in Europe date back to the mid-19th century, but it was only recorded as a breeding species in the early 1960s in Portugal and a few years later in neighbouring Spain. This recent colonization, possibly from Africa where the species is abundant, may be due to climate change, land-use changes in southern Europe, or both. As a ﬁrst step to understanding this range expansion process we have developed a habitat selection model using data from the current strongholds of its European distribution. Comparing the proportion of different habitat types around 46 breeding sites and 45 randomly chosen plots, we have found that the area of cultivated parklands known as dehesas in Spain is a strong predictor of the current distribution range of breeding pairs of Black-shouldered Kites. Speciﬁcally, the percentage of dehesas with planted cereal and a low density of trees (i.e. < 7 trees/ha and thus a savannah-like habitat) within the study plots explained 44.6% of the residual deviance in our model. The minimal adequate model classiﬁed 81.3% of breeding sites and random plots correctly. Our results suggest that Black-shouldered Kites may have taken advantage of the gradual increase of cultivated dehesas in the second half of the 20th century to expand its range in Europe. This particular type of dehesa is structurally similar to the African savannahs where the species thrives and may offer a higher density of rodents than traditional dehesas, which primarily contain pastureland for livestock ranching
Keywords: colonization; Dehesa; habitat selection; Land-use change; occurrence models; raptors.

Land-use changes may explain the recent range expansion of the Black-shouldered Kite Elanus caeruleus in southern Europe - Balbontín, Javier; Negro, Juan José; Sarasola, José Hernán; Ferrero, Juan José; Rivera, Domingo (Ibis, 2008)
Occasional observations of Black-shouldered Kites Elanus caeruleus in Europe date back to the mid-19th century, but it was only recorded as a breeding species in the early 1960s in Portugal and a few years later in neighbouring Spain. This recent colonization, possibly from Africa where the species is abundant, may be due to climate change, land-use changes in southern Europe, or both. As a ﬁrst step to understanding this range expansion process we have developed a habitat selection model using data from the current strongholds of its European distribution. Comparing the proportion of different habitat types around 46 breeding sites and 45 randomly chosen plots, we have found that the area of cultivated parklands known as dehesas in Spain is a strong predictor of the current distribution range of breeding pairs of Black-shouldered Kites. Speciﬁcally, the percentage of dehesas with planted cereal and a low density of trees (i.e. < 7 trees/ha and thus a savannah-like habitat) within the study plots explained 44.6% of the residual deviance in our model. The minimal adequate model classiﬁed 81.3% of breeding sites and random plots correctly. Our results suggest that Black-shouldered Kites may have taken advantage of the gradual increase of cultivated dehesas in the second half of the 20th century to expand its range in Europe. This particular type of dehesa is structurally similar to the African savannahs where the species thrives and may offer a higher density of rodents than traditional dehesas, which primarily contain pastureland for livestock ranching
Keywords: colonization; Dehesa; habitat selection; Land-use change; occurrence models; raptors.

La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S.; Vendramin, G. G. (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
The following values have no corresponding Zotero field: pub-location: (1) CNR Istituto per la Protezione delle Piante, via Madonna del Piano, Edificio E, 50019 Sesto Fiorentino, Firenze; (2) CNR Istituto di Genetica Vegetale, sezione di Firenze, via Madonna del Piano, Edificio D, 50019 Sesto Fiorentino, Firenze publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus

La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S; Vendramin, G G (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus

Efecto de la inoculación de cuatro bacterias promotoras del crecimiento vegetal sobre parámetros biométricos aéreos de plántulas de QUERCUS ILEX SSP.BALLOTA B. - Ramos, B; Lucas García, J A; Santamaría, C; Camacho, M; Daza, a; García, J A Lucas (III Congreso Forestal Español Congreso, 2001)
In the present work has studied the effect of four plant growth-promoting rhizobacteria (PGPRs) on growth of holm-oak plants (Quercus ilex ssp. ballota) in nursery before transplanting. The four strains assayed show in vitro metabolic capacities related with their action PGPR. All strains were able to increase significantly some parameters studied (high, diameter neck and dry weight). However, in the first sampling time (T1) only the strains Aur 6 and Aur 9 increased the high of the plants. In the last sampling time (T3) all strains increased the high, only Aur 6 increased the diameter neck and Cell 3, Aur 6 and Aur 9 increased the dry weight. It is important to point out that Aur 6 and Aur 9 increased the high and also the dry weight, this show that these strains enhance the general metabolism of the plants and also enhance the nutritional capacity and as a result the plants are more robust and with a better adaptative capacity.
Keywords: adaptative capacity; colonization; PGPR; Quercus ilex ssp. ballota

Efecto de la inoculación de cuatro bacterias promotoras del crecimiento vegetal sobre parámetros biométricos aéreos de plántulas de QUERCUS ILEX SSP.BALLOTA B. - Ramos, B.; Lucas García, J. A.; Santamaría, C.; Camacho, M.; Daza, A.; García, J. A. Lucas (III Congreso Forestal Español Congreso, 2001)
In the present work has studied the effect of four plant growth-promoting rhizobacteria (PGPRs) on growth of holm-oak plants (Quercus ilex ssp. ballota) in nursery before transplanting. The four strains assayed show in vitro metabolic capacities related with their action PGPR. All strains were able to increase significantly some parameters studied (high, diameter neck and dry weight). However, in the first sampling time (T1) only the strains Aur 6 and Aur 9 increased the high of the plants. In the last sampling time (T3) all strains increased the high, only Aur 6 increased the diameter neck and Cell 3, Aur 6 and Aur 9 increased the dry weight. It is important to point out that Aur 6 and Aur 9 increased the high and also the dry weight, this show that these strains enhance the general metabolism of the plants and also enhance the nutritional capacity and as a result the plants are more robust and with a better adaptative capacity.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso issue: 1 pub-location: Granada
Keywords: adaptative capacity; colonization; PGPR; Quercus ilex ssp. ballota